Rising Rates of Caesarean Section in Urban Nepal - Dhakal Rai, Sulochana; Regmi, Pramod Raj; Teijlingen, Edwin van; Wood, Juliet; Dangal, Ganesh; Dhakal, Keshar Bahadur (Journal of Nepal Health Research Council, 2019)
The rising rate of caesarean section in urban Nepal is alarming as the lack of access for women in rural areas to emergency obstetric care, putting lives at risk. The latter is referred to as ‘Too little too late’. At the same time, the sharp rise in caesarean section rates in cities presents the other extreme: “Too much too soon”. The overuse of caesarean section causes harm, unnecessary costs, and misuse of health resources. Availability of private hospitals and increasing hospital childbirth may contribute to the rising rate of caesarean section. This article highlights the rising rate of caesarean section in urban Nepal. Keywords: Caesarean section; emergency obstetric care; Nepal.